2023
DOI: 10.1007/s44297-023-00006-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbe-mediated nanoparticle intervention for the management of plant diseases

Temoor Ahmed,
Jinyan Luo,
Muhammad Noman
et al.

Abstract: Plant diseases are caused by various pathogenic microorganisms, leading to substantial economic losses and food insecurity worldwide. However, the extensive use of chemical-based nanopesticides has adverse effects on plants, soil, and environmental systems. There is increasing interest in developing eco-friendly and sustainable alternatives to manage plant diseases. Recently, microbe-mediated nanoparticles (NPs) as nanopesticides have attracted the interest of cultivators, specifically in plant disease managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 114 publications
0
1
0
Order By: Relevance
“…Therefore, there is a need for alternative control methods to fight these diseases and limit their spread and damage. Recently, nanoparticles have attracted the attention of many scientists working in a variety of disciplines, including those in the agricultural sector interested in plant disease suppression due to their unique properties [ 17 , 18 , 19 ]. Many of them have observed that silver nanoparticles (AgNPs) have a distinct role against a wide range of microorganisms, such as viruses, bacteria, and fungi, which infect and damage plants [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a need for alternative control methods to fight these diseases and limit their spread and damage. Recently, nanoparticles have attracted the attention of many scientists working in a variety of disciplines, including those in the agricultural sector interested in plant disease suppression due to their unique properties [ 17 , 18 , 19 ]. Many of them have observed that silver nanoparticles (AgNPs) have a distinct role against a wide range of microorganisms, such as viruses, bacteria, and fungi, which infect and damage plants [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%